Modernism as Institution On the Establishment of an Aesthetic and Historiographic Paradigm - Hayden, Hans (Stockholm Studies in Culture and Aesthetics, 2018)
"Anyone who studies the history of modern art-in art museums, in the classroom, in art historical handbooks or specialist surveys-will soon be aware of a certain recurrent pattern governing the selection of objects and forming a certain type of narrative where the history of modern art is presented as a variety of different -isms that dissolve into each other in the coherent sequence that constitutes the history of modern art as modernism. But why is this pattern so similar in all different places and contexts? Is it possible to distinguish between the history of modern art and the history of modernism? And if so, when, where and how did modernism become synonymous with art of the modern era? With a dual perspective-regarding art as well as the discursive perception of art-Modernism as an Institution attempts to answer these questions by studying the frameworks for the institutional establishment, as well as the historiography, of modern art."